2020
DOI: 10.3389/fpsyg.2020.567499
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Environmental Stimulation in Anorexia Nervosa: An Early-Phase Clinical Trial

Abstract: Reduced Environmental Stimulation Therapy (REST) alters the balance of sensory input to the nervous system by systematically attenuating sensory signals from visual, auditory, thermal, tactile, vestibular, and proprioceptive channels. Previous research from our group has shown that REST via floatation acutely reduces anxiety and blood pressure (BP) while simultaneously heightening interoceptive awareness in clinically anxious populations. Anorexia nervosa (AN) is an eating disorder chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…As a consequence, mechanical, thermal, visual, and acoustic stimuli are reduced to a minimum. Previous studies have shown positive effects of flotation-REST, such as increased relaxation, 13 lowered stress levels, 14,15 improved sleep quality, 16 reduced anxiety, 14,15,17,18 and pain relief. 15,19 These studies, however, differed in design, sample size, inclusion criteria, and dosage of flotation-REST, which hinders their comparison.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As a consequence, mechanical, thermal, visual, and acoustic stimuli are reduced to a minimum. Previous studies have shown positive effects of flotation-REST, such as increased relaxation, 13 lowered stress levels, 14,15 improved sleep quality, 16 reduced anxiety, 14,15,17,18 and pain relief. 15,19 These studies, however, differed in design, sample size, inclusion criteria, and dosage of flotation-REST, which hinders their comparison.…”
Section: Introductionmentioning
confidence: 91%
“…As a consequence, mechanical, thermal, visual, and acoustic stimuli are reduced to a minimum. Previous studies have shown positive effects of flotation-REST, such as increased relaxation, lowered stress levels, improved sleep quality, reduced anxiety, and pain relief …”
Section: Introductionmentioning
confidence: 98%
“…Specifically related to cardiovascular changes that occur as the result of Floatation-REST, several studies have reported significant reductions in both systolic and diastolic blood pressure when comparing measurements taken before and after a float session (Jacobs et al, 1984;Turner et al, 1989). More recently, our lab has found significant blood pressure reductions during the actual float session, with diastolic blood pressure showing the largest decrease when compared to watching a nature documentary (Feinstein et al, 2018b) or lying supine in a zero-gravity chair (Khalsa et al, 2020). Two previous studies explored the effects of Floatation-REST on heart rate (Forgays and Belinson, 1986;O'Leary and Heilbronner, 1990) with variable results.…”
Section: Introductionmentioning
confidence: 96%
“…This window into ANS functioning in the absence of sensory stimulation could provide a novel paradigm for measuring an 10.3389/fnins.2022.995594 individual's true physiologic baseline, one that is untethered from the influences of the external world. However, the baseline state engendered by floating is not affectively neutral, as prior research has shown that the float experience induces a state of serenity and decreased anxiety, effects that were most pronounced in clinically anxious patients (Feinstein et al, 2018a,b;Khalsa et al, 2020). Notably, all of the patients had high levels of anxiety sensitivity, which refers to one's fear of experiencing anxiety-related symptoms and sensations, especially those arising from within the body (Taylor, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation